Розробка компонентів інформаційної системи магазину сільськогосподарської техніки - Крапівін, А. В. (ХНУРЕ, 2025)
This paper examines the process of creating an e-commerce information system for an agricultural machinery shop. Mentioned system is designed to be an easy way of displaying and searching the products as well as placing and managing the orders of the store. The relevance of such system is to satisfy the growing demand for sales automation in the agricultural machinery sector. The creation of web application will be done using Java programming language wІТh Spring Boot Framework, Thymeleaf template engine and MySQL database platform.
Keywords: магазин техніки; сільськогосподарська техніка